Sjögren’s Disease and Gastroesophageal Reflux Disease: What Is Their Evidence-Based Link? - Diana Mieliauskaitė; Vilius Kontenis (Medicina)
Sjögren’s disease (SjD), or primary Sjögren’s syndrome (pSS), is a heterogeneous chronic autoimmune disorder with multiple clinical manifestations that can develop into non-Hodgkin’s lymphoma in mucosa-associated lymphoid tissue. SjD is one of the autoimmune diseases with the maximum delayed diagnosis due to its insidious onset, heterogeneous clinical features and varied course. It is increasingly recognized that extraglandular manifestations represent a clinical challenge for patients with SjD. The European League Against Rheumatism (EULAR) Sjögren’s Syndrome (SS) Disease Activity Index (ESSDAI) is a systemic disease activity index designed to measure disease activity in patients with primary Sjogren’s syndrome. It consists of 12 domains: cutaneous, pulmonary, renal, articular, muscular, peripheral nervous system, central nervous system, hematological, glandular, constitutional, lymphadenopathy and lymphoma, biological. More than a quarter of patients with pSS may have systemic features that are not included in the ESSDAI classification, i.e., various cardiovascular, ophthalmic, ENT, and other systemic or organ involvement that increase the magnitude of the systemic phenotype in the disease. The ESSDAI also excludes the gastrointestinal (GI) tract, and unfortunately, GI manifestations are not routinely assessed. Gastroesophageal reflux disease (GERD) is one of the most prevalent gastrointestinal disorders, impairing quality of life and consuming a large volume of medical resources. Recently carried out the Mendelian randomized trial confirmed the causal link between SjD and gastroesophageal reflux disease (GERD) and showed that GERD is a risk factor for SjD. This review aims to provide an overview of the research describing evidenced based links between Sjögren’s disease and gastroesophageal reflux disease, with the intention of ensuring that any systemic pathology in Sjögren’s disease is properly assessed and that management of the disease is directed towards the patient. A comprehensive literature search was carried out on PubMed, Web of Science, Scopus and the Cochrane Library databases. Two researchers searched for published studies indexed from inception to 1 September 2024 using the keywords ‘Sjögren’s syndrome’ OR ‘Sjögren’s disease’ AND ‘gastroesophageal reflux disease’ AND ‘microbiota’ OR microbiota dysbiosis’. We limited our search for scientific articles to human studies, and only included articles in English. Overall, there is a lack of evidence-based studies assessing the association between GERD and Sjögren’s disease and the changes in the microbiota associated with GERD in a multidisciplinary setting. Such studies are needed for the future, as this will improve the early diagnosis of Sjögren’s disease and the personalized management of the disease.